Expression 5: "y" Subscript, "s" , Baseline equals "P" . "y" minus left parenthesis, "P" . "x" minus "x" Subscript, "s" , Baseline , right parenthesis squaredys=P.y−P.x−xs2
equals=
44
5
`x_s=${x_s}` "X" equals left parenthesis, "x" Subscript, "s" , Baseline , 0 , right parenthesisX=xs,0
Label:
6
Expression 7: "x" equals "x" Subscript, "s" , Baselinex=xs
equals=
33
7
`c=${c}` "Y" equals left parenthesis, 0 , "c" , right parenthesisY=0,c
Label:
8
Expression 9: "c" equals 1c=1
negative 10−10
1010
9
Expression 10: "b" equals StartFraction, "P" . "y" minus "P" . "x" squared minus "c" Over "P" . "x" , EndFractionb=P.y−P.x2−cP.x